Relationship between the Ecological Factors with Community Stucture of Mangrove in Pang-Pang Bay Alas Purwo National Park - Acik, Rifan; Sudarmadji, Sudarmadji (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
The Mangrove ecosystem has benefits, one of them as the buffer ecosystem. This research has purpose to know the relationship between community structure of Mangrove and the ecologycal factor in Pangpang bay, Alas Purwo National Park. The result from this research are Rhizophora apiculata has highiest INP is 96,44, Sonneratia alba has lowest INP is 35,47. Dominance indeks had by Ceciops tagal is 4,70. Diversity indeks of stiks Mangroves shown low value with Shanon Weiner (H') <0,32. Result of community coefisien shown that Rhizophora apiculata is 0,315. The result is ecologycal factor community structure have relation significantly.